The relationship between the risk of the asset and its expected rate of return: a case of stock exchange market of five European countries. (1st October 2016) - Khudoykulov, Khurshid; Allado`stov, Rustam; Khalikov, Ulugbek
Abstract: The study proposes to verify the capital asset pricing model (CAPM) and its validity for stock markets in the selected European countries' stock markets: Greece, Italy, Poland, Portugal, and Czech Republic. We examined the top 40 companies listed in the five European countries through a data-set collected on a weekly basis from January 2009 to December 2013. The CAPM model is tested by performing a two-stage regression methodology using Eviews. We performed a first-stage regression to estimate stocks of the beta through a linear regression. After that, we used a second-stage cross-sectional regression to estimate the relationship of the average return of the portfolio and its beta. It is concluded that there is no relationship between average return of the portfolio and its beta. However, we only found that there was a linear relationship between the expected returns and beta of the Italian stock market. The negative relationship does not support the CAPM theory. Therefore, it is concluded that the CAPM does not hold for the selected sample of the five European countries' stock markets.